Proving in Zero-Knowledge that a Number is the Product of Two Safe Primes - Camenisch, Jan; Michels, Markus (BRICS Report Series, 1998)
This paper presents the first efficient statistical zero-knowledge protocols to prove statements such as: A committed number is a pseudo-prime. A committed (or revealed) number is the product of two safe primes, i.e., primes p and q such that (p - 1)=2 and (q - 1)=2 are primes as well. A given value is of large order modulo a composite number that consists of two safe prime factors. So far, no methods other than inefficient circuit-based proofs are known for proving such properties. Proving the second property is for instance necessary in many recent cryptographic schemes that rely on both the hardness of computing discrete logarithms and of difficulty computing roots modulo a composite. The main building blocks of our protocols are statistical zero-knowledge proofs that are of independent interest. Mainly, we show how to prove the correct computation of a modular addition, a modular multiplication, or a modular exponentiation, where all values including the modulus are committed but not publicly known. Apart from the validity of the computation, no other information about the modulus (e.g., a generator which order equals the modulus) or any other operand is given. Our technique can be generalized to prove in zeroknowledge that any multivariate polynomial equation modulo a certain modulus is satisfied, where only commitments to the variables of the polynomial and a commitment to the modulus must be known. This improves previous results, where the modulus is publicly known. We show how a prover can use these building blocks to convince a verifier that a committed number is prime. This finally leads to efficient protocols for proving that a committed (or revealed) number is the product of two safe primes. As a consequence, it can be shown that a given value is of large order modulo a given number that is a product of two safe primes. Keywords. RSA-based protocols, zero-knowledge proofs of knowledge, primality tests.